Reinterpretasi Mustahiq al-Zakah Sebagai Solusi Pengentasan Kemiskinan - Samheri S.HI M.Sh (STIU Al-Mujtama Pamekasan, 2019)
Abstract:The writing of scientific papers regarding the zakat has been writen by many experts, but based on the author's observation, there is no writing that criticizes the attitude and behavior and or public perception of mustahiq al-zakah which is considered still too normative and conventional, so the maqashid shariah of zakat has not rialized. Therefore, the writer need to reinterpret the meaning of mustahiq al-zakah to find a solution and realize the purpose of zakat legalities. This research uses qualitative research method, with phenomenological approach. The author tries to adjust and search for new meanings to prioritize mustahiq al-zakah that is more in need and need it, like the word riqab that can not be found anymore in real life in various hemispheres anywhere. Also meaning sabilillah and ibn sabil are considered too broad and less relevant to the intent and purpose of zakat, so zakat has not felt to provide a solution to the true mustahiq. In addition, the zakat allocation for converts is considered unnecessary, given that Islam is currently not a weak person who needs financial aid to meet the needs of his life. It was also be done by Umar bin Khattab during his life. Keywords: reinterpret, mustahiq zakah, maqa>sid shari>ah